Autonomic regulation of T-lymphocytes: Implications in cardiovascular disease. (August 2019) - Elkhatib, Safwan K.; Case, Adam J.
Graphical abstract: Abstract: The nervous and immune systems both serve as essential assessors and regulators of physiological function. Recently, there has been a great interest in how the nervous and immune systems interact to modulate both physiological and pathological states. In particular, the autonomic nervous system has a direct line of communication with immune cells anatomically, and moreover, immune cells possess receptors for autonomic neurotransmitters. This circumstantial evidence is suggestive of a functional interplay between the two systems, and extensive research over the past few decades has demonstrated neurotransmitters such as the catecholamines ( i.e. dopamine, norepinephrine, and epinephrine) and acetylcholine have potent immunomodulating properties. Furthermore, immune cells, particularly T-lymphocytes, have now been found to express the cellular machinery for both the synthesis and degradation of neurotransmitters, which suggests the ability for both autocrine and paracrine signaling from these cells independent of the nervous system. The details underlying the functional interplay of this complex network of neuroimmune communication are still unclear, but this crosstalk is suggestive of significant implications on the pathogenesis of a number of autonomic-dysregulated and inflammation-mediated diseases. In particular, it is widely accepted that numerous forms of cardiovascular diseases possess imbalanced autonomic tone as well as altered T-lymphocyte function, but a paucity of literature exists discussing the direct role of neurotransmitters in shaping the inflammatory microenvironment during the progression or therapeutic management of these diseases. This review seeks to provide a fundamental framework for this autonomic neuroimmune interaction within T-lymphocytes, as well as the implications this may have in cardiovascular diseases.